Manipulation of Quercetin and Melatonin in the Down-Regulation of HIF-1α, HSP-70 and VEGF Pathways in Rat's Kidneys Induced by Hypoxic Stress - Aliah R. Alshanwani; Sameerah Shaheen; Laila M. Faddah; Ahlam M. Alhusaini; Hanaa M. Ali; Iman Hasan; Hanan Hagar; Raeesa Ahmed; Fatima M. B. Alharbi; Alaa AlHarthii (SAGE Publishing, 2020)
Hypoxia may lead to inflammatory responses by numerous signaling pathways. This investigation intended to inspect the defensive role of Quercetin (Quer) and/ or Melatonin (Mel) against reno toxicity induced by Sodium nitrite (Sod ntr). Sod ntr injection significantly decreased blood hemoglobin concentration (Hb) with a concurrent increase in serum tumor necrosis factor- α, interleukin-6, C-reactive protein, creatinine, and urea levels. Over protein-expression of vascular endothelial growth factor and heat shock, protein-70 and mRNA of HIF-1α were also observed. Pretreatment of the Sod ntr- injected rats with the aforementioned antioxidants; either alone or together significantly improved such parameters. Histopathological examination reinforced the previous results. It was concluded that the combined administration of Quer and Mel may be useful as a potential therapy against renal injury induced by Sod ntr. HIF-1α and HSP-70 are implicated in the induction of hypoxia and its treatment.